Reservoir quality of the Stø and Nordmela Formations in well 7220/8-1, Johan Castberg Area in the SW Barents Sea. - Khan, Asad (2016)
This project aims to increase the understanding of reservoir quality of the Stø and Nordmela Formations in the Skrugard well (7220/8-1) in the SW Barents Sea. The selected interval from 1292.3 m to 1404.25 m in the Skrugard well has been examined through X-ray diffraction, scanning electron microscope, petrophysical and petrographic analysis. The interval has experienced significant uplift. The Stø Formation and the upper part of Nordmela Formation contain very fine to fine and moderately to well-sorted sandstone. Most of the interval was deposited during highstand conditions. It mainly consists of shoreface to far shoreface sandstone with minor estuarine deposits. The lower portion of the Nordmela Formation has tidal influenced heterogeneous lithology. The conglomeratic lag is found within the Nordmela Formation in this well is unlike the other wells. The Stø and the upper part of Nordmela Formations have high porosity and permeability. Gamma ray response is low in the Stø Formation and high in the lower part of the Nordmela Formation due to its heterolithic origin. There is no specific trend between porosity and depth because of the restricted temperature interval (112 m thick sediments which corresponds to 3 ºC). The rock has experienced higher mechanical stress and initial chemical cementation before it was uplifted. At current position, it has a higher mechanical strength than what is necessary to hold the overburden. High values of intergranular volume (25.81%) and p-waves velocity (3000-3500 m/s) are also associated with stiffening of grain framework. IGV is affected by grain size, grain sorting and primary clay content. Most of the interval consists of clean sandstone with little depositional matrix (with average percentages of 1.75%) and cement (4.89%) and has high porosity of around 19.27%. Porosity is main contributor in IGV and is not affected by minor amount of clays present. Quartz cementation and overgrowth is mostly sourced by the smectite to illite alteration.